Manajemen Risiko Divisi Sistem Informasi Pada Universitas Bina Insan Menggunakan Framework Cobit 5 - Juminovario Juminovario; Edi Surya Negara (CogITo Smart Journal, 2022)
Bina Insan University has done a lot of development on the progress of information technology, especially information systems, as an example with the Academic System/academic portal. Puskom translates UnivBi's vision and mission into an information technology innovation. UnivBi Puskom Unit, it is realized that there are a number of things that have not been maximized, this is due to the small number of employees who have the ability to deal with risks that may occur suddenly and the unavailability of standard procedure documents for handling risk, and an assessment of the level of risk capability has not been carried out so that risk control is not yet implemented. goes well. To support this research, several previous research results are referred to as the basis for IT risk management analysis activities. From the results of this study, it was found that Bina Insan University had implemented the Ensure Risk Optimation and Risk Management processes, this was evidenced by the results of capability at level 3, which means the process was performed, but Bina Insan University had not been optimal in its operation. The gap value resulting from the APO12 domain is 1 and the EDM03 domain is 2. This gap value indicates that the condition of information system governance at Bina Insan University is still not good and does not match what is targeted by the University